Out of the Sweatshop: The Struggle for Industrial Democracy - Dussault, Gilles (Relations industrielles / Industrial Relations, 1978)
This article reviews "Out of the Sweatshop: The Struggle for Industrial Democracy" edited by Leon Stein.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z